Supporting organizational professional culture with collaborative technology during design phase in industrialized project delivery in Malaysia - R., Ibrahim; Abdul Ghafar, M. (Springer Nature, 2022)
Smart cities development would change the way how architects, engineers and contractors (AEC) professionals do their work during industrialized project delivery (IPD) in the future. The purpose of this case study research is to distinguish the base line communication preferences that could aid policy makers and building professionals to prepare themselves to deliver the smart city implementation. The study found that AEC’s professional culture, methods of knowledge transfer and educational programs could affect several dimensions of their beliefs and values in ways of delivering projects. The results of triadic rework iterations are recommended for the implementation in the design of multidisciplinary design studio education program as part of the future Malaysian AEC transdisciplinary training for smart cities deployment. The paper supports CITP 2016–2020’s Strategic Thrusts 1, 3 and 4 for the Malaysian construction industry. The paper documents the human process of IPD during design development stage. Future studies are recommended to assess actual implementation and use IBS system in design studio setting.